Komparasi Phantom Berbasis Agar dan Minyak dalam Pengujian Vertical Distance dan Horizontal Distance pada Perangkat USG - Pramesti Kusumaningtyas Kusumaningtyas; Imam Tri Harsoyo; Mohamad Sofie; Iqbal Dwiky Septyawan (Jurnal Teori dan Aplikasi Fisika, 2026)
Ultrasound phantom is an important tool in simulation, training, and calibration of ultrasound devices. This study aims to compare the performance of agar and oil-based ultrasound phantoms using vertical distance and horizontal distance parameters. Both types of phantoms are made by embedding test objects in the form of nylon ropes in their respective media. Evaluation is carried out by measuring the vertical and horizontal distances displayed on the ultrasound image, then compared with the actual distance. The results show that the oil phantom produces measurement deviations that are still within acceptable tolerance limits. The oil-based phantom shows more stable and accurate results. Thus, the oil-based phantom is considered superior and more recommended for use in simulation and testing of ultrasound devices.   Keywords: USG phantom, vertical distance, horizontal distance, agar-based phantom, oil-based phantom.